A METHOD OF INCREASING THE INTEGRITY OF INFORMATION STORED IN DATA STORAGE SYSTEMS BY COMBINING SYNDROME AND PROBABILISTIC DECODING - Alina A. Lanina; Alla B. Levina (Безопасность информационных технологий)
In today's world, the amount of information to be stored is increasing. Such information can be stored in data centers - information processing centers. In this regard, there is a need to use specialized data storage systems (DSS) capable of storing such volumes of information. In them failures may occur due to problems with the network, power supply and, as a consequence, a part of the stored information may be distorted or lost. Errors may occur in the stored information - these may be errors in reading or writing operations or errors occurring during storage due to external impact on the disk and wear of its mechanisms, in case of damage of data transmission channels. Data integrity control in storage systems is carried out through regular checks and automatic error detection, which allows to timely identify and eliminate problems in the stored information. The purpose of the work is to increase the number of correctable errors in stored information. A method of increasing the integrity of information stored in data storage systems by combining syndrome and soft decoding has been developed. The developed method has been implemented in Python programming language. The proposed method is described in detail. The results of comparison of the proposed combination method, its components and information recovery by standard RAID means are given, showing that the proposed method has better characteristics of operation time and number of corrected errors, compared to the methods included in the combination individually and the standard information recovery mechanisms provided in the RAID array.